Dukungan Keluarga bagi Self Care Management Behaviour pada Klien Hipertensi - Noverizah, Efita; Hartati, Elis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between family support and self-care management behavior in hypertensive clients. The research method uses a correlation research design with a cross-sectional approach. The results showed that most hypertensive clients have sufficient family support (61.5%) and good self-care management behavior (86.2%). The results of the Spearman rank correlation test, the majority of clients have sufficient family support and good self-care management behavior (57.7%), the correlation level is in the weak category, and the direction of the relationship is positive with a value of r = 0.278 and p-value = 0.001 (p <0.05). In conclusion, there is a relationship between family support and self-care management behavior in hypertensive clients in the weak category and the direction of the relationship is positive. Keywords: Family Support, Hypertension, Self Care Management Behavior